2017
DOI: 10.18632/oncotarget.20497
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress-induced JNK/AP-1 signaling is a major pathway involved in selective apoptosis of myelodysplastic syndrome cells by Withaferin-A

Abstract: Myelodysplastic syndromes (MDS) are a diverse group of malignant clonal hematopoietic stem cell disorders characterized by ineffective hematopoiesis, dysplastic cell morphology in one or more hematopoietic lineages, and a risk of progression to acute myeloid leukemia (AML). Approximately 50% of MDS patients respond to current FDA-approved drug therapies but a majority of responders relapse within 2-3 years. There is therefore a compelling need to identify potential new therapies for MDS treatment. We utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Taken together, these results showed that Wi-A caused oxidative stress leading to ROS generation. This was in line with a previous report that also showed that activation of, c-Jun N-terminal kinase/Activator protein 1 (JNK/AP-1) mediated apoptosis signaling in response to ROS [92]. Other studies have reported that Wi-A induces inhibition of proteasomal degradation resulting in accumulation of ER chaperones (BiP and GRP94) and cytoplasmic heat shock proteins [93].…”
Section: Discussionsupporting
confidence: 92%
“…Taken together, these results showed that Wi-A caused oxidative stress leading to ROS generation. This was in line with a previous report that also showed that activation of, c-Jun N-terminal kinase/Activator protein 1 (JNK/AP-1) mediated apoptosis signaling in response to ROS [92]. Other studies have reported that Wi-A induces inhibition of proteasomal degradation resulting in accumulation of ER chaperones (BiP and GRP94) and cytoplasmic heat shock proteins [93].…”
Section: Discussionsupporting
confidence: 92%
“…Relative gene expression through the JNK pathway, a key mediator of inflammatory signaling in MDS. [33][34][35] Gerstung et al 25 showed that GRID1 expression is significantly (P 5 .013) upregulated (by 0.023) in association with DNMT3A mutations, a commonly found MDS driver mutation that should be explored in the context of the loci identified here. GRID1 introns encode microRNAs critical for unfolded protein response (UPR).…”
Section: Relative Gene Expressionmentioning
confidence: 76%
“…Previously, the forced expression of c-Jun and c-Fos has induced apoptosis in neuronal cells [ 47 , 48 ]. Additionally, treatment of myelodysplastic cells with the plant-derived compound, withaferin A, caused an increase in the mRNA expression of JUN and FOS and their subsequent protein expression and resulted in downstream activation of apoptosis [ 49 ]. More specifically, Ren et al [ 33 ] were able to show that increasing the expression of c-Jun and c-Fos in MIA PaCa-2 cells caused the downstream induction of apoptosis via activation of Bim and the subsequent effect on Bcl-2 family proteins.…”
Section: Discussionmentioning
confidence: 99%